Determinants involved in the construction of the violence of gender. The case of the primary schools in a province of Spain - Emilia Moreno Sánchez; Carmen Márquez Vázquez (Arizona State University, 2016)
In this work we present a descriptive correlational study that took place in some primary schools of Huelva (Andalusia, Spain) financed with public funds, in which gender differences in the comprehension of violence at primary school are analyzed. With the information obtained, we can conclude with the fact that the violence perceived by students in the educative environment has a clear component of gender and in both sexes internalization is showed since their childhood. They reproduce models of differential socialization between boys and girls. Because of this, it is necessary to create a debate in the school's community and an involvement of the gender's perspective in teaching, training and researching and especially in educative politic in order to progress towards the equal rights between men and women since their childhood.